Role of gut microbiota in the postnatal thermoregulation of Brandt’s voles - Tingbei Bo; Liqiu Tang; Xiaoming Xu; Min Liu; Jing Wen; Jinzhen Lv; Dehua Wang (Cell Reports, 2023)
Summary: Homeothermy is crucial for mammals. Postnatal growth is the key period for young offspring to acquire gut microbiota. Although gut microbiota may affect mammal thermogenesis, the impact of developmental regulation of gut microbiota on the ability of young pups to produce heat remains unclear. Antibiotics were used to interfere with the establishment of gut microbiota during the development of Brandt’s voles, and their thermogenic development and regulatory pathways were determined. Deprivation of microbiota by antibiotics inhibits the development of thermogenesis in pups. Butyric acid and bile acid, as metabolites of gut microbiota, participated in the thermoregulation of pups. We propose that gut microbiota promote the development of thermoregulation through the butyric acid-free fatty acid receptor-2-uncoupling protein-1 or the deoxycholic acid-Takeda-G-protein-receptor-5-uncoupling protein-1 pathway in pups. These results show a relationship between gut microbiota and thermogenesis and expand the mechanism of postnatal development of thermogenesis in small mammals.